A Custom-made MATLAB Based Software to Manage Leakage Current Waveforms - Pylarinos, D. (Engineering, Technology & Applied Science Research, 2011)
Leakage current (LC) monitoring is a widely employed tool for monitoring the performance of high voltage insulators. LC waveform monitoring is required to acquire a view of the phenomena experienced since the type of LC waveform’s shape is correlated with different types of electrical activity. In case of field monitoring, specially designed measuring systems, capable of operating under field conditions, have to be installed. The Greek Public Power Corporation (PPC) has issued a large project for monitoring the performance of outdoor insulators. A commercially available LC measuring system, was purchased and installed by PPC. The system was able to monitor various outdoor insulators, record several statistical values and intermittently record a LC waveform. The provided software lacked some capabilities that were required for certain research areas and a custom made software had to be developed. In this paper, two stand-alone MATLAB based softwares, “Leakage Current Waveform File Converter” and “Leakage Current Waveform Viewer”, both equipped with a user friendly GUI, are presented. The first software was developed in order to automatically convert multiple files from the CSV format (as extracted from the measuring system) to the MAT format in order to allow data compactness and further processing. The latter software was developed in order to offer a tool for collective viewing, printing and extraction to JPEG format, of LC waveforms in groups of user-defined numbers. The latter function gives the opportunity for easy and fast creation of waveform archives.